1997
DOI: 10.1128/cmr.10.1.185
|View full text |Cite
|
Sign up to set email alerts
|

PCR in laboratory diagnosis of human Borrelia burgdorferi infections

Abstract: The laboratory diagnosis of Lyme borreliosis, the most prevalent vector-borne disease in the United States and endemic in parts of Europe and Asia, is currently based on serology with known limitations. Direct demonstration of Borrelia burgdorferi by culture may require weeks, while enzyme-linked immunosorbent assays for antigen detection often lack sensitivity. The development of the PCR has offered a new dimension in the diagnosis. Capable of amplifying minute amounts of DNA into billions of copies in just a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
79
1
13

Year Published

1999
1999
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 152 publications
(94 citation statements)
references
References 180 publications
(240 reference statements)
1
79
1
13
Order By: Relevance
“…However, this is unlikely, since all synovial samples spiked with B burgdorferi sensu lato DNA indicated the absence of such PCR inhibitors. We cannot completely exclude the possibility that the method of DNA extraction or the low frequency of the genetic target chosen in this study may have resulted in a false-negative result, although the sensitivity of the PCR with RLB used in this study was comparable with that found in most other studies (44).…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…However, this is unlikely, since all synovial samples spiked with B burgdorferi sensu lato DNA indicated the absence of such PCR inhibitors. We cannot completely exclude the possibility that the method of DNA extraction or the low frequency of the genetic target chosen in this study may have resulted in a false-negative result, although the sensitivity of the PCR with RLB used in this study was comparable with that found in most other studies (44).…”
Section: Discussionmentioning
confidence: 46%
“…Another cause that should be considered as an explanation for the negative PCR result in the 1 patient with Lyme arthritis is interference by host DNA in the Lyme-specific PCR (44). However, this is unlikely, since all synovial samples spiked with B burgdorferi sensu lato DNA indicated the absence of such PCR inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, a variety of PCR assays aimed to detect Lyme borrelia DNA in clinical specimens have been developed and evaluated for their diagnostic value in patients with different clinical manifestations of Lyme borreliosis. Many technical details and applications of PCR assays were addressed in several recently published reviews (Schmidt, 1997;Bunikis and Barbour, 2002;Wang, 2002;Dumler, 2003;Wilske, 2003;Aguero-Rosenfeld et al, 2005).…”
Section: Nucleic Acid Amplification Of Lyme Borrelia Dnamentioning
confidence: 99%
“…A variety of clinical specimens from patients with suspected Lyme borreliosis have been analyzed by PCR assays (Schmidt, 1997;Aguero-Rosenfeld et al, 2005). Of these, skin biopsy samples taken from patients with EM were the most frequently tested specimens Wienecke et al, 1993;Muellegger et al, 1995Muellegger et al, , 1996von Stedingk et al, 1995;Picken et al, 1997;Rijpkema et al, 1997;Brettschneider et al, 1998;Oksi et al, 2001;Liveris et al, 2002;Wang, 2002).…”
Section: Nucleic Acid Amplification Techniquesmentioning
confidence: 99%
See 1 more Smart Citation